Cuestiones institucionales en e! Acuerdo de 1994 relativo la parte XI de la Convención sobre el Derecho del Mar - Paolillo, Felipe H. (Estudios Internacionales, 1995)
The Agreement of July 1994 introduced profound changes in the rules of Part XI of the Convention on the Law of the Sea that regulate the procedures for the adoption of decisions in the Assembly and the Council, the composition of the latter and the distribution of powers between the two organs. As a result of these changes, the supremacy that the Council in fact had over the Assembly (only formally "the supreme organ" in the Convention system) is accentuated and the position within the first of the industrialized countries is strengthened, which have now with the possibility of controlling and guiding the management of the Authority.